Proteomic Discovery of VEEV E2-Host Partner Interactions Identifies GRP78 Inhibitor HA15 as a Potential Therapeutic for Alphavirus Infections - Michael D. Barrera; Victoria Callahan; Ivan Akhrymuk; Nishank Bhalla; Weidong Zhou; Catherine Campbell; Aarthi Narayanan; Kylene Kehn-Hall (Pathogens, 2021)
Alphaviruses are a genus of the Togaviridae family and are widely distributed across the globe. Venezuelan equine encephalitis virus (VEEV) and eastern equine encephalitis virus (EEEV), cause encephalitis and neurological sequelae while chikungunya virus (CHIKV) and Sindbis virus (SINV) cause arthralgia. There are currently no approved therapeutics or vaccines available for alphaviruses. In order to identify novel therapeutics, a V5 epitope tag was inserted into the N-terminus of the VEEV E2 glycoprotein and used to identify host-viral protein interactions. Host proteins involved in protein folding, metabolism/ATP production, translation, cytoskeleton, complement, vesicle transport and ubiquitination were identified as VEEV E2 interactors. Multiple inhibitors targeting these host proteins were tested to determine their effect on VEEV replication. The compound HA15, a GRP78 inhibitor, was found to be an effective inhibitor of VEEV, EEEV, CHIKV, and SINV. VEEV E2 interaction with GRP78 was confirmed through coimmunoprecipitation and colocalization experiments. Mechanism of action studies found that HA15 does not affect viral RNA replication but instead affects late stages of the viral life cycle, which is consistent with GRP78 promoting viral assembly or viral protein trafficking.